Implementasi Layanan PDP di Layanan Kesehatan Primer Kabupaten Banyumas - Evicenna Naftuchah Riani; Dewi Ambarwati; Dzikria Afifah Primala Wijaya (2022)
HIV / AIDS is increasing year by year the incidence of transmission and death. In Indonesia, it is a health problem that must be handled intensively. The high mortality rate of people living with HIV/AIDS is due to non-optimal management of patients. Various factors influence the increase in morbidity and mortality of HIV/AIDS. Care, support and treatment (PDP) services are integrated and continuous services to provide support to PLWHA in managerial, medical, psychological and social aspects to reduce problems encountered during care and treatment. The cumulative number of PLWHA found in Banyumas Regency in 2006 - August 2021 was 3,958 cases, who met the requirements for ARV therapy as many as 2,447 cases and 2,521 cases who had access to ARV. Of the 2,521 people living with HIV who accessed ARVs, only 773 cases were currently on ARVs, 453 cases died, 6 cases stopped ARVs, 1178 lost follow-up (LFU) cases and 423 cases were referred out. This study is a qualitative research that aims to explore the implementation of PDP services in primary services in Banyumas Regency. The method of data collection was carried out by in-depth interviews. There were 7 informants in this study, namely 4 counselors as primary informants and secondary informants, 2 coordinator midwives and 1 PLWHA. Data analysis in this qualitative research uses thematic content analysis. The results showed that the implementation of PDP services in primary services in Banyumas district was quite good, indicated by the availability of adequate supporting infrastructure. Health workers who work in PDP services have a counselor training certificate. Constraints that are not yet able to assist clients.